ROBUSTA COFFEE MARKETING EFFICIENCY ANALYSIS IN PASEMAH AIR KERUH DISTRICT, EMPAT LAWANG REGENCY - Fadmawaty Fadmawaty; Amruzi Minha; Desi Aryani (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Pasemah Air Keruh District is one of the biggest Robusta coffee-producing areas in Empat Lawang Regency. This research aims to (1) determine the channels and marketing functions; (2) determine the structure, conduct, and performance of the market. Sampling methods used were snowball and simple random sampling. The data analysis methods used were (1) descriptive analysis to explain the channels and marketing functions; (2) structure, conduct, and performance analysis to explain marketing efficiency based on surveys, observations, and interviews using a questionnaire. The results showed that there are two marketing channels, (1) coffee farmers - village collecting traders - district collecting traders - wholesalers - exporters; (2) coffee farmers - retailers - consumers. The marketing functions are not fully carried out by marketing agencies. The market structure is oligopsony. The market conduct shows that price is dominated by middlemen, limited market information, and the absence of government policy on coffee prices. The market performance shows high marketing margins, an uneven margin distribution, low farmers’ share, and a low K/B ratio. It means that coffee marketing is inefficient. The government should make policies that encourage the coffee sector to become a large- scale business, such as making regulations, expanding access to capital, domestic and export market networks.